A scoping review of interventions to promote voluntary donation of human breast milk in India - Jisha B. Krishnan; Vijay Shree Dhyani; Ravi Shankar Swamy; Nachiket Gudi (Clinical Epidemiology and Global Health, 2023)
Purpose: To map the interventions that have been implemented to promote voluntary human milk donation in India. Methods: A search was conducted on four electronic databases to locate studies published in English, from 2011 to 2022. We followed Arskey and O'Malley's ScR guidelines. Results: Four studies were included in this review. Interventions included PDSA cycles based on “quality improvement”, one to one lactation counseling, group counseling and focused counseling. Improvement in voluntary milk donation was observed in all four studies. Conclusion: The limited evidence demonstrated the need for curating more awareness interventions related to human milk donation and its usability.